STUDY OF SOME PHYSICAL PROPERTIES OF BRIQUETTES FROM DIFFERENT FOREST WOODY BIOMASS COLLECTIONS IN KURDISTAN REGION OF IRAQ - yaseen, dilgash; Abdulqader, Aree; Abdullah, Ahmed (Science Journal of University of Zakho, 2025)
By using forest waste, energy sustainability can be improved, and biomass briquettes offer a sustainable and eco-friendly substitute for fossil fuels. This study examines the physical characteristics of briquettes made from various woody biomass species, as a result of assessing factors including the amount of moisture, density, shatter resistance, tumble resistance, and resistance to water penetration. Also, to identify ideal production circumstances, in both tree species (Quercus infectoria and Pinus brutia). Factors were particle size (2 and 4 mm), moisture levels (6, 9, and 12%), and briquetting temperature (330 and 350 °C). According to the results, Quercus infectoria briquettes processed at 350 °C, with particle sizes of 2 mm and moisture levels of 6%, showed enhanced physical characteristics and combustion efficiency. Longer burning times were caused by higher compactness, and storage stability was improved by resistance to water penetration. These results offer insightful information for the biofuel sector, assisting producers in improving their methods of production to produce premium, environmentally friendly biomass briquettes. The study advances the larger objective of lowering reliance on energy sources that are not renewable and advancing sustainable energy solutions by enhancing the durability and efficiency of biomass fuels. The findings support more investigation into improving biomass briquetting procedures for increasing environmental and financial advantages